Corrections of myocardial tissue sodium concentration measurements in human cardiac 23Na MRI at 7 Tesla. Issue 1 (12th March 2019) - Lott, Johanna; Platt, Tanja; Niesporek, Sebastian C.; Paech, Daniel; G. R. Behl, Nicolas; Niendorf, Thoralf; Bachert, Peter; Ladd, Mark E.; Nagel, Armin M.
Abstract : Purpose: To quantify the tissue sodium concentration (TSC) in cardiac 23 Na MRI. To evaluate the influence of different correction methods on the measured myocardial TSC. Methods: 23 Na MRI of four healthy subjects was conducted at a whole‐body 7T MRI system using an oval‐shaped 23 Na birdcage coil. Data acquisition was performed with a density‐adapted 3D radial pulse sequence using a golden angle projection scheme. 1 H MRI data were acquired at a 3T MRI system to generate a myocardial mask. Retrospective cardiac and respiratory gating were used to reconstruct 23 Na MRI data in the diastolic phase and exhaled state. B0 and B1 inhomogeneity and partial volume (PV) effects were corrected. Relaxation times and TSC of ex vivo blood samples and calf muscle were determined. These values were used in the PV correction to estimate myocardial TSC, which was compared with the measured TSC of calf muscle. Results: Without any correction the measured myocardial TSC was (54 ± 5) mM. The applied correction methods reduced these values by (48 ± 5)% to (29 ± 3) mM, where PV correction had the largest effect (reduction of (34 ± 1)%). Respiratory and cardiac motion gating decreased the concentrations by (11 ± 1)%. With the applied setup, the corrections of B0 and B1 inhomogeneity (reduction of (3 ± 2)%) had negligible influences on TSC values. The resulting myocardial TSC was approximately 1.4‐fold higher than the measured TSC of calf muscle tissue of the same healthy subjects ((20 ± 3) mM). Conclusion: For quantitative human cardiac 23 Na MRI several corrections are needed and ranked for our setup: PV correction, respiratory and cardiac gating, correction for B1 inhomogeneity effects.